(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
A simple, accurate and precise stability indicating method was developed for the simultaneous estimation of the encorafenib (ECRB) and binimetinib (BMTB) in a dosage form by UPLC. Chromatographic elution was processed through a HSS C18 (100 x 2.1 mm, 1.8m) reverse phase column and the mobile phase composition of 0.01N KH2PO4 buffer (3.5 pH) and acetonitrile in the proportion of 55:45 was processed thru a column at a flow rate of 1.0 ml/min. Temperature of the column oven was kept at 30.0°C and the wavelength maximum of detection system was set to 294 nm. Retention times of ECRB and BMTB were found to be 0.767 min and 1.130 min respectively. Repeatability of the method was determined in the form of %RSD and findings were 0.3 and 0.6 for ECRB and BMTB respectively. The percentage recovery of the method was found to be 99.59% and 99.70% for ECRB and BMTB respectively. LOD, LOQ values obtained from regression equations of ECRB and BMTB were 0.51, 1.55mg/ml and 1.47, 4.44 mg/ml respectively. Regression equation of ECRB was y = 6684.x + 18102 and BMTB was y = 13118x + 2159. Two analytes were subjected for acid, peroxide, photolytic, alkali, neutral and thermal degradation studies and the results shown that the percentage of degradation was found between 0.76% and 6.88%. Retention times and total run time of two drugs were decreased and the developed method was simple and economical. So, the developed method can be adopted in industries as a regular quality control test for the quantification of ECRB and BMTB.